2021
DOI: 10.1002/adfm.202104887
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Based Nanomaterials for Neuroengineering: Recent Advances and Future Prospective

Abstract: Graphene unique physicochemical properties made it prominent among other allotropic forms of carbon, in many areas of research and technological applications. Interestingly, in recent years, many studies exploited the use of graphene family nanomaterials (GNMs) for biomedical applications such as drug delivery, diagnostics, bioimaging, and tissue engineering research. GNMs are successfully used for the design of scaffolds for controlled induction of cell differentiation and tissue regeneration. Critically, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 130 publications
0
14
0
Order By: Relevance
“…In the last two decades, tremendous progress has been made. However, the use of most of the new nanomaterials is limited due to toxicity and low biodegradability [6]. Recently, the interest in the field of biodegradable components has increased because of the possibility of tailoring their properties and biodegradation characteristics [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, tremendous progress has been made. However, the use of most of the new nanomaterials is limited due to toxicity and low biodegradability [6]. Recently, the interest in the field of biodegradable components has increased because of the possibility of tailoring their properties and biodegradation characteristics [7].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of GBMs with neurons and astrocytes is still poorly investigated and unclear, due to the variable methods for GBM production that influence the oxygen content, lateral size, contaminants, and number of layers [ 155 ]. In one of the earlier studies, Defterali et al using rGO showed good neuronal and glial biocompatibility [ 156 , 157 ]. It seems plausible that carbon nanomaterial might modulate neuroinflammation, a common feature of neurodegenerative diseases [ 158 ].…”
Section: Approaches For Mirna Therapeutic Deliverymentioning
confidence: 99%
“…With the growing use of graphene materials, there are parallel public concerns about the safety of their release into the environment [ 10 ]. In contrast to the long-term and in-depth research that has been conducted into GFN exposure in animals [ 2 , 11 , 12 , 13 , 14 , 15 ], studies into the effects of GFNs on plants are just beginning.…”
Section: Introductionmentioning
confidence: 99%